ACHESYM: an algorithm and server for standardized placement of macromolecular models in the unit cell - Kowiel, Marcin (Acta Crystallogr D Biol Crystallogr, 2014)
Despite the existence of numerous useful conventions in structural crystallography, for example for the choice of the asymmetric part of the unit cell or of reciprocal space, surprisingly no standards are in use for the placement of the molecular model in the unit cell, often leading to inconsistencies or confusion. A conceptual solution for this problem has been proposed for macromolecular crystal structures based on the idea of the anti-Cheshire unit cell. Here, a program and server (called ACHESYM; http://achesym.ibch.poznan.pl) are presented for the practical implementation of this concept. In addition, the first task of ACHESYM is to find an optimal (compact) macromolecular assembly if more than one polymer chain exists. ACHESYM processes PDB (atomic parameters and TLS matrices) and mmCIF (diffraction data) input files to produce a new coordinate set and to reindex the reflections and modify their phases, if necessary.